The protection of minority rights: a comparative survey with special reference to South Africa's constitutional options - Van Rooyen, Johann (Department of Political Studies, 2016)
The purpose of this dissertation is firstly to define and analyse the concept of minority rights and to place it in perspective in relation to surrounding concepts such as communalism, ethnicity, groups and individualism. This is done through a critical discussion of various theoretical perspectives relating to the subject matter. Comparisons are drawn between the policies of various plural societies aimed at accommodating their ethnic diversity, either constitutionally or through methods that lack legitimacy. This is followed by a discussion and evaluation of consociational democracy and federalism as possible solutions to the problems created by ethnicity and minorities in a plural society. Having made the hypothesis that democracy is best served in a multi-ethnic society by a system that emphasizes group rights in addition to individual rights and which accepts the notion of government through consensus, the emphasis then moves to the particular nature of the South African minority question. The policies of the various actors on the South African political scene towards minority rights are analysed critically. Attention is given to factors which may influence group formation in a system emphasizing voluntary association, such as race, ethnicity, class and ideology. There is also a discussion of the nature of the rights which minorities may claim and emphasis is placed on the requirement that minorities should be able to levy strategic influence without disrupting the society as a whole. Finally, this dissertation deals with the question of which constitutional alternatives offer the most promising solution to the problems caused by South Africa's cultural diversity. Although a political system emphasizing individual rights might come closest to the liberal ideal and may be suitable to an ethnically homogeneous country, the violent history of plural societies where group rights have been neglected, indicate the need for a pluralist solution in South Africa. While there is a strong tendency among Blacks to view the concept of minority rights as yet another Apartheid ploy to maintain White domination and privileges, the purpose of this paper has been to prove that minority rights is a universal concept and is not a creation of Apartheid, although the National Party has managed to almost irreversibly taint it. Yet, in a system of group formation through voluntary association, the concept of minority rights can serve as a powerful tool to help facilitate a negotiated settlement towards a predominantly Slack government based on consensus. A true power-sharing consensus-orientated constitution has been found in Lijphart's notion of a consociational democracy and the view is taken that the Natal-KwaZulu Indaba's constitutional proposals is an example of such a constitution.